2022
DOI: 10.1108/sjls-02-2022-0013
|View full text |Cite
|
Sign up to set email alerts
|

The barefoot shoemaker's son: examining EFL teachers' pragmatic competence in a Saudi context

Abstract: PurposeEnglish instructors' pragmatic competence (PC) is an aspect of the overall communicative competence forming the basis of language instructors' knowledge. Their knowledge of pragmatics should not be overlooked when seeking to understand foreign language learners' communicative ability. This study aims to investigate the pragmatic awareness and teaching practices of non-native EFL instructors with different qualifications and from various cultural backgrounds in Saudi Arabia.Design/methodology/approachTo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…8 Though English training is intended to assist students develop proficiency in communicating, insufficient pragmatics education for students learning EFL could result in poor communication skills. 9 In a comparable line, Farahian et al suggested that in order to acquire communicative competence, participants first need to enhance their pragmatic competence, which may be assisted by educators. 10 According to Thomas in Grossi, the capacity for successful communication requires knowledge that goes beyond grammar.…”
Section: Introductionmentioning
confidence: 99%
“…8 Though English training is intended to assist students develop proficiency in communicating, insufficient pragmatics education for students learning EFL could result in poor communication skills. 9 In a comparable line, Farahian et al suggested that in order to acquire communicative competence, participants first need to enhance their pragmatic competence, which may be assisted by educators. 10 According to Thomas in Grossi, the capacity for successful communication requires knowledge that goes beyond grammar.…”
Section: Introductionmentioning
confidence: 99%